Investigations of the failure behaviors of open-cell copper foam based on in-situ X-ray tomography compression experiments and image reconstructed finite element modeling. (15th March 2022) - Ni, Yunzhu; Liao, Haitao; Zhao, Quanyue; Wu, Wenwang; Shi, Yi; Wu, Shengchuan
Highlights: In situ compression experiments are performed for exploring the deformation features and internal local failure behaviors of open-cell copper foams. Four types of geometrical components are identified in the open-cell copper foam. Three different finite element models are constructed based on tomography images and compared with experimental results. Simulation and experimental results confirm that plastic strain localization features are closely related to the initial spatial orientation of struts. Abstract: Multifunctional open-cell copper foams are widely used in different industrial sections and are featured by their topological microstructures, thus generating robust mechanical properties, sound absorption, and thermal conductivity. In this paper, making use of 3D imaging techniques based on micro-CT X-Ray tomography, in situ compression experiments are performed for exploring the deformation features and internal local failure behaviors of open-cell copper foams. During the in-situ compression process, geometrical topological features of deformed samples at different strain levels were reconstructed based on 3D X-ray computed tomography images, and four types of geometrical components were identified in the open-cell copper foam samples, namely strut, node, closed-cell and groove, respectively. Afterwards, several types of finite element models are constructed, finite element analysis is performed and compared with experiments for understanding the deformation process for porous copper samples. In order to improve the mesh quality of finite element models reconstructed from X-Ray tomography images, the mesh was generated through surface fitting technique. Then, the generated mesh was imported into finite element analysis software ABAQUS/Explicit for numerical simulation, simulation results suggest that large amounts of plastic strain localization and structure collapses are formed during the compression process, and such plastic strain localization features are closely related to the initial spatial orientation of struts.